Hypoglycemia assessed by continuous glucose monitoring is associated with preclinical atherosclerosis in individuals with impaired glucose tolerance. - Ersilia Castaldo; Donata Sabato; Davide Lauro; Giorgio Sesti; Maria Adelaide Marini (PLoS ONE, 2011)
Hypoglycemia is associated with increased risk of cardiovascular adverse clinical outcomes. There is evidence that impaired glucose tolerance (IGT) is associated with cardiovascular morbidity and mortality. Whether IGT individuals have asymptomatic hypoglycemia under real-life conditions that are related to early atherosclerosis is unknown. To this aim, we measured episodes of hypoglycemia during continuous interstitial glucose monitoring (CGM) and evaluated their relationship with early manifestation of vascular atherosclerosis in glucose tolerant and intolerant individuals. An oral glucose tolerance test (OGTT) was performed in 79 non-diabetic subjects. Each individual underwent continuous glucose monitoring for 72 h. Cardiovascular risk factors and ultrasound measurement of carotid intima-media thickness (IMT) were evaluated. IGT individuals had a worse cardiovascular risk profile, including higher IMT, and spent significantly more time in hypoglycemia than glucose-tolerant individuals. IMT was significantly correlated with systolic (r = 0.22; P = 0.05) and diastolic blood pressure (r = 0.28; P = 0.01), total (r = 0.26; P = 0.02) and LDL cholesterol (r = 0.27; P = 0.01), 2-h glucose (r = 0.39; P<0.0001), insulin sensitivity (r = -0.26; P = 0.03), and minutes spent in hypoglycemia (r = 0.45; P<0.0001). In univariate analyses adjusted for gender, minutes spent in hypoglycemia were significantly correlated with age (r = 0.26; P = 0.01), waist circumference (r = 0.33; P = 0.003), 2-h glucose (r = 0.58; P<0.0001), and 2-h insulin (r = 0.27; P = 0.02). In a stepwise multivariate regression analysis, the variables significantly associated with IMT were minutes spent in hypoglycemia (r(2) = 0.252; P<0.0001), and ISI index (r(2) = 0.089; P = 0.004), accounting for 34.1% of the variation. Episodes of hypoglycemia may be considered as a new potential cardiovascular risk factor for IGT individuals.